Pedicle Corridors and Vessel Options for Free Flap Reconstruction following Endoscopic Endonasal Skull Base Surgery: A Systematic Review - Dang, Rajan P.; Roland, Lauren T.; Sharon, Jeffrey D.; Doering, Michelle; Chicoine, Michael R.; Pipkorn, Patrik (Journal of Neurological Surgery Part B: Skull Base, 2019)
Introduction Microvascular free flaps offer an alternative to local and regional flaps for coverage of complex or large skull base defects. Routes and approaches to these reconstructive options are complicated and require an understanding of complex head and neck anatomy.Methods A systematic review of the literature was performed using a set of search terms with the help of a qualified librarian. Articles were reviewed and selected for inclusion based on relevance. We were interested in reporting possible routes for free flap accessibility to the skull base as well as microvascular vessel options, as this choice may affect the geometry and accessibility to the defect.Results A total of 1,917 articles were obtained from a comprehensive search and 11 articles were ultimately found to be relevant to this review. Published options for vessel anastomosis and corridors to the skull base following endoscopic endonasal surgery are reviewed, including Caldwell-Luc/transbuccal space, prevertebral space, transpterygoid/parapharyngeal, and transmaxillary approaches.Conclusion The field of endoscopic surgery has continued to advance and provide options for tumors of the skull base. This has led to a need for creative routes to the skull base for free flap reconstruction.
Keywords: endoscopic; skull base; free flap; reconstruction